Genome‐wide analysis on Chlamydomonas reinhardtii reveals the impact of hydrogen peroxide on protein stress responses and overlap with other stress transcriptomes. (December 2015) - Blaby, Ian K.; Blaby‐Haas, Crysten E.; Pérez‐Pérez, María Esther; Schmollinger, Stefan; Fitz‐Gibbon, Sorel; Lemaire, Stéphane D.; Merchant, Sabeeha S.
Summary: Reactive oxygen species (ROS) are produced by and have the potential to be damaging to all aerobic organisms. In photosynthetic organisms, they are an unavoidable byproduct of electron transfer in both the chloroplast and mitochondrion. Here, we employ the reference unicellular green alga Chlamydomonas reinhardtii to identify the effect of H2 O2 on gene expression by monitoring the changes in the transcriptome in a time‐course experiment. Comparison of transcriptomes from cells sampled immediately prior to the addition of H2 O2 and 0.5 and 1 h subsequently revealed 1278 differentially abundant transcripts. Of those transcripts that increase in abundance, many encode proteins involved in ROS detoxification, protein degradation and stress responses, whereas among those that decrease are transcripts encoding proteins involved in photosynthesis and central carbon metabolism. In addition to these transcriptomic adjustments, we observe that addition of H2 O2 is followed by an accumulation and oxidation of the total intracellular glutathione pool, and a decrease in photosynthetic O2 output. Additionally, we analyze our transcriptomes in the context of changes in transcript abundance in response to singlet O2 ( O 2 * ), and relate our H2 O2 ‐induced transcripts to a diurnal transcriptome, where we demonstrate enrichments of H2 O2 ‐induced transcripts early in the light phase, late in the light phase and 2 h prior to light. On this basis several genes that are highlighted in this work may be involved in previously undiscovered stress remediation pathways or acclimation responses. Significance Statement: Oxidative stress negatively affects all aerobic and photosynthetic organisms but the detoxification systems and how they are regulated are not fully understood. Here we used RNA‐Seq and comparative transcriptomics to document mRNA abundance changes in C. reinhardtii exposed to hydrogen peroxide and thereby identified previously undiscovered stress remediation pathways.